Women in Political Bodies as Policymakers - Thushyanthan Baskaran; Zohal Hessami (Institute of Labor Economics (IZA), 2023)
We investigate how female representation impacts policymaking using the example of child care and new hand-collected data on local council elections in Bavaria. RDD estimations (mixed-gender races for last party-specific council seats) show that an additional female councilor accelerates the expansion of public child care by 40%. We also document an important nonlinearity: an additional woman accelerates the expansion of child care only in councils with few women. Council meeting minutes reveal that women can be effective in councils despite being a non-pivotal minority because they change "the conversation".
Keywords: D72; D78; H70; J13; J16; 330; gender composition; political selection; local councils; child care